Certain aspects of guidance at the Baguio City High School - Atanacio, Fe B. 1920- ([Quezon City s.n.], 1968)
The study analyzed certain aspects of guidance at the Baguio City High in order to determine its implications. The questions considered involve the extent of guidance consciousness among personnel, the extent of teacher participation in guidance, the teacher's attitude toward guidance and the obtained results from the administration of appraisal measures to the students.
Thesis (M.Ed.)--University of the Philippines
Keywords: Baguio City High School -- Students; Personnel service in education